Cumplimiento de normas y estándares en los procesos del data center del departamento de coordinación de tecnología de la ESPAM MFL - Alcívar Alcívar, Maria Alexandra (2017)
The evaluation of the fulfillment of rules and standards in the processes of the Data Center of the Department of Technology Coordination and the Institutional Web Page of the ESPAM MFL allowed to determine the threats and risks existing when not having a suitable guide for the management of these. In the titling work the PMBOK was used as a reference guide as it provides a framework for any type of project. Once the methodology was determined, it was necessary to gather information regarding the current processes of the aforementioned unit. Subsequently, questionnaires were elaborated based on the IT internal control standards of the Comptroller General of the Ecuadorian State. Additionally, international quality standards were considered such as: ISO / IEC 25010, ANSI / TIA - 942 standard and COBIT methodology, these were used as a good practice reference. These questionnaires were applied and the results obtained were analyzed. Statistical measures were used, weaknesses were detected in the preparation of contingency plans, policies, among others, through questionnaires applied to users. It was also determined that the institutional website has a rating of 7.22, that is, it is on an acceptable scale. Once the investigation was completed, a report was issued along with an improvement plan, establishing recommendations, such as documenting the flaws encountered.